Penerapan Sistem Informasi Penelitian Internal Di Politeknik Negeri Indramayu Menggunakan Metode Kanban - A Sumarudin; Amirrudin; Adi Suheryadi (SOTVI - Society of Visual Informatics, 2021)
The internal research information system is an application that is used to manage research proposal data within the scope of the Indramayu State Polytechnic (POLINDRA) starting from submission, assessment, implementation to reporting. At first the system at the Indramayu State Polytechnic was still not well integrated in terms of submitting proposals from lecturers, because the sending process was still using email. Then the approval process for the proposal will be seen by external reviewers. Furthermore, the self-assessment process is carried out by filling out the assessment form provided by P3M, then it will be sent to the Reviewer via email. The choice of a website system for the development of this application is not only easier to operate and the flexible nature of the website is one of the reasons. The problem raised in this topic is that the submission of proposals is still manual using email so that data errors may still occur, data is lost or damaged. With this application, it is expected to be able to manage the proposed data so that it is fast, efficient and optimally the data stored in the system. Making this application using the Kanban method. This application is also built using the Laravel Framework and MariaDB Database. The tests carried out in this study used black-box testing with the results of testing the available features successfully and the program running well. With the Internal Research Information System through the proposal feature that displays a list of existing research proposals to the proposer. So that in sending, evaluating proposals and managing research proposals so that the process of sending, evaluating and approving proposals submitted by lecturers at the Indramayu State Polytechnic becomes easier, faster, efficient, and well integrated.